Respuesta :
simply appply the chain rule over and over again
f'(g(x))=f'(g(x))g'(x)
first derivitive would be f'(x)=4(2x+1)³(2) or 8(2x+1)³
2nd derivitive would be 24(2x+1)²(2) or 48(2x+1)²
3rd derivitive would be 96(2x+1)2 or 192(2x+1)
4th derivitive would be 192(1)(2) or 384
at x=0, the derivitive is 384
f'(g(x))=f'(g(x))g'(x)
first derivitive would be f'(x)=4(2x+1)³(2) or 8(2x+1)³
2nd derivitive would be 24(2x+1)²(2) or 48(2x+1)²
3rd derivitive would be 96(2x+1)2 or 192(2x+1)
4th derivitive would be 192(1)(2) or 384
at x=0, the derivitive is 384
The 4th derivative of [tex]f(x)[/tex] at [tex]x=0[/tex] is 384.
Given:
The given function is:
[tex]f(x)=(2x+1)^4[/tex]
To find:
The 4th derivative of [tex]f(x)[/tex] at [tex]x=0[/tex].
Explanation:
Differentiate the given function with respect to [tex]x[/tex].
[tex]f'(x)=4(2x+1)^3(2x+1)'[/tex]
[tex]f'(x)=4(2x+1)^3(2)[/tex]
[tex]f'(x)=8(2x+1)^3[/tex]
Differentiate the above function with respect to [tex]x[/tex].
[tex]f''(x)=8\cdot 3(2x+1)^2(2x+1)'[/tex]
[tex]f''(x)=24(2x+1)^2(2)[/tex]
[tex]f''(x)=48(2x+1)^2[/tex]
Differentiate the above function with respect to [tex]x[/tex].
[tex]f'''(x)=48\cdot 2(2x+1)^1(2x+1)'[/tex]
[tex]f'''(x)=96(2x+1)^1(2)[/tex]
[tex]f'''(x)=192(2x+1)[/tex]
Differentiate the above function with respect to [tex]x[/tex].
[tex]f''''(x)=192(2+0)[/tex]
[tex]f''''(x)=384[/tex]
At [tex]x=0[/tex], the value of [tex]f''''(0)=384[/tex]. Therefore, the required value is 384.
Learn more:
https://brainly.com/question/17298632